The dual education program in Egypt: a qualitative study on challenges and opportunities - Sherif, Ahmed Maher (AUC Knowledge Fountain, 2013)
The Mubarak Kohl Initiative – now called the Dual Education System is considered as one of the most successful intervention of active labor market programs (ALMPs) in Egypt. The Dual Education Program offers a unique type of education that includes on-the-job training. Students can learn, work and earn in addition to a guaranteed job opportunity upon graduation. The blue collar category is normally the poor people who suffer from a low social standard as well as low income. The Dual Education System mainly targets technical and vocational workers to promote their living standard. Technical and Vocational Education in Egypt occupies the least governmental attention in regards to its improvement and budget allocation. This thesis will give an overview on governmental expenditure on technical and vocational education in Egypt. Also, it will point out the importance of the Dual Education System initiative in promoting the vocational and technical professions in Egypt and providing better job opportunities for its graduates and how far this is actually accomplished in reality and the key behind the project's sustainability. It will also point out the main lessons to be learnt from the Dual Education System, how it can be replicated by other interventions and how the program is evolving in its current scale-up phase. It will also show why preparatory students join the Dual Education System although they do not intend to continue in technical and vocational jobs.